(untitled) (Comprehensive Journal of Science, 2025)
This descriptive-analytical study aimed to evaluate mothers’ awareness and practices related to breastfeeding and weaning in Misrata, Libya. A random sample of 210 mothers with children under the age of two was included. The results showed that a substantial proportion of mothers initiated breastfeeding within the first few hours after delivery (25.2% immediately after birth and 28.6% within the first hours). The majority practiced mixed feeding (71.9%), with insufficient breast milk supply reported as the primary reason for using formula. Regarding weaning, most mothers (56.7%) adopted a gradual approach, which is recommended from both psychological and health perspectives to support the child’s emotional and physical development. Statistical analysis revealed significant associations between breastfeeding and weaning practices and several factors, including the child’s birth order, mode of delivery, maternal age, educational level, and household income. These findings emphasize the need to strengthen maternal health education programs to improve breastfeeding and weaning practices, especially considering the heavy reliance on nonmedical sources of information. The study recommends implementing continuous awareness initiatives to enhance knowledge and promote healthier infant feeding behaviors, thereby contributing to improved child health and development outcomes